2021
DOI: 10.1186/s12903-021-01839-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the position and morphology of tongue and hyoid bone in skeletal Class II malocclusion based on cone beam computed tomography

Abstract: Background The aim of the study was to analyze the morphology and position of the tongue and hyoid bone in skeletal Class II patients with different vertical growth patterns by cone beam computed tomography in comparison to skeletal Class I patients. Methods Ninety subjects with malocclusion were divided into skeletal Class II and Class I groups by ANB angles. Based on different vertical growth patterns, subjects in each group were divided into 3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
2
8
0
1
Order By: Relevance
“…Future longitudinal studies are necessary to clarify the causal relationship. Additionally, the hyoid bone and cranium measurements were two-dimensional, and three-dimensional measurements could be used to explore the relationship between the bilateral TMJ and the position and size of the hyoid bone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future longitudinal studies are necessary to clarify the causal relationship. Additionally, the hyoid bone and cranium measurements were two-dimensional, and three-dimensional measurements could be used to explore the relationship between the bilateral TMJ and the position and size of the hyoid bone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esto se debería a las relaciones musculares que entrega el triángulo hioideo (Lowell, Kelley, Colton, Smith, & Portnoy, 2012). En este caso, el patrón esqueletal, la posición de la lengua o la postura cervical, pueden mantener a este hueso elevado y provocar cambios supraglóticos naturales y funcionales (Şahin Sağlam & Uydas, 2006;Urzal, Braga, & Ferreira, 2014;Chen, Mou, Qian, & Qian, 2021). Tanto el grado de entrenamiento vocal, como aspectos craneocervicales o estomatognáticos no fueron evaluados en las mujeres participantes en esta investigación, lo que se convierte en una importante limitación para estimar con mayor precisión la aparición de compresiones supraglóticas en el G1.…”
Section: Discussionunclassified
“…Sample size was calculated using a formula proposed by Pandis [19] with power = 80%, level of significance = 0.05, to detect a difference of 4.44 mm in H-V distance between MB and NB and standard deviation = 4.2 mm [13]. We found that 14 subjects on each subgroup would be sufficient.…”
Section: Sample Size Calculationmentioning
confidence: 98%
“…CBCT offered more precise information than lateral cephalogram (LC) [12]. Most previous studies used LC to determine HBP, and few of them used CBCT [13][14][15][16][17][18]. However, the effect of breathing mode on HBP using CBCT has never been studied previously.…”
Section: Introductionmentioning
confidence: 99%